The Confession of King Gälawdewos (r. 1540–1559): A Sixteenth-Century Ethiopian Monophysite Document against Jesuit Proselytism - Solomon Gebreyes Beyene (Aethiopica, 2022)
The Jesuit mission in Ethiopia represented one of the most serious challenges of Ethiopian Christianity during the early modern times. The mission had two phases. In the first phase, from 1555 to 1603, the missionaries undertook to convert King Gälawdewos and his court in return for military support from Portugal but had to face opposition from his successor, Minas (r.1559–1563). The second period ran from 1603 to 1632 and marked the major success of the mission. The missionaries managed to convert King Susənyos (r.1607–1632) as well as important nobles and dignitaries. In the first phase of the mission, even though the Christian kingdom had been heavily weakened by the wars with Imām Aḥmad b. Ibrāhīm al-Ġazī, called ‘Grañ’ by Christians, the political and religious leaders resolutely opposed Jesuit proselytism. Their opposition took the form of theological debates, wherein local religious leaders, including the ruler, confronted the foreigners and their alien dogmas. In this paper, I will analyse a contemporary Ethiopian religious text popularly known as the Confession of King Gälawdewos. The piece was composed in 1555 under the order of Gälawdewos to face the Jesuit challenge. The paper will show that this important literary work was instrumental in defending the indigenous Orthodox religion and local customs.